Study of lip prints: A forensic study - Vikash Ranjan; Mysore K Sunil; Raghav Kumar (Wolters Kluwer Medknow Publications, 2014)
Background: Although several studies have been done on lip prints for human identification in forensic science, there is a doubt about their use in gender determination. Aims: The present study was designed to study the lip groove patterns in all the quadrants of both male and female subjects to identify the sex, based on the patterns of the grooves of the lip prints. Study Design: 300 lip prints were collected from volunteers of D. J. College of Dental Sciences and Research, Modinagar (UP). Materials and Methods: Lip prints were recorded with lip stick and transferred on to a glass slide. Statistical Analysis: Pearson chi-square test was adopted for statistical analysis and probability value (P value) was calculated. Conclusion: In our study, none of the lip prints were identical, thus confirming the role of lip prints in individual identification. According to Suzuki's classification, Type I, II, III and IV patterns were significant in gender determination.